2017
DOI: 10.1016/j.jpubeco.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Clean up your own mess: An experimental study of moral responsibility and efficiency

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…[2015]; Jakob et al . [2017]; or see Sturm and Weimann [2006] and Croson and Treich [2014] for reviews of this literature). Our experiment also relates to earlier experiments on dynamic optimization (Chermak and Krause [2002]; Fischer et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…[2015]; Jakob et al . [2017]; or see Sturm and Weimann [2006] and Croson and Treich [2014] for reviews of this literature). Our experiment also relates to earlier experiments on dynamic optimization (Chermak and Krause [2002]; Fischer et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The matching of judges and producers to markets for the determination of experimental payoffs was implemented in the following way: after producers' decisions were collected, one producer with a valuation equal to each of the 10 values in the interval of [3 Euro;12 Euro] was randomly picked and assigned to one market. Due to the ex-ante uncertain number of experimental producers, we were not always able to form complete markets with exactly 10 producers.…”
Section: Methodsmentioning
confidence: 99%
“…Most previous experimental studies on emissions markets centered on details of specific market designs 9 , yet these studies do not consider the externality caused by trading in emission markets 10 . Some recent experiments have provided evidence of a willingness to pay a premium for a positive environmental impact 11 and for a motivation to remove negative externalities 12 . Finally, some studies have elicited individuals' willingness to pay to avoid real-world CO2 emissions [13][14][15][16][17] .…”
Section: Pricing Mechanisms and Co2 Externalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same vein, Sandel ( 2012 ), raises fundamental moral objections to market mechanisms. Moreover, in an experimental setting, Jakob et al ( 2017 ) have shown that market-based policies, while efficient, conflict with moral behavior. According to the authors, moral responsibility induced study participants to take inefficient actions that reduced the earnings of the whole group of participants.…”
Section: Barriers To Implementing Pigouvian Taxes and Subsidiesmentioning
confidence: 99%